2004
DOI: 10.2188/jea.14.1
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Child Sleep Diary Questionnaire among Junior High School Children

Abstract: BACKGROUND: The validity of sleep quality and quantity indices as reported by schoolchildren has not been established. The purpose of this study is to evaluate the relationship between subjective sleep habits estimation and objective measurement data in schoolchildren. METHODS: The study consisted of 42 healthy junior high school children aged 13-14. Sleep log information was gathered over 7 consecutive days, using a sleep-monitoring device (Actiwatch ® ) and a questionnaire w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 10 publications
3
58
0
2
Order By: Relevance
“…[38][39][40] There is evidence that subjective and objective sleep variables in adolescents, including sleep start time, sleep end time, and sleep duration, were highly correlated. 41 Our previous study also reported good agreement between actigraphy-measured and subjectively reported sleep duration (intraclass correlation coefficient = 0.72). 3 Polysomnography and ABPM were performed only at a single time point, which hindered a better understanding of the association between changes in sleep duration, sleep architecture, and BP.…”
Section: Figuresupporting
confidence: 61%
“…[38][39][40] There is evidence that subjective and objective sleep variables in adolescents, including sleep start time, sleep end time, and sleep duration, were highly correlated. 41 Our previous study also reported good agreement between actigraphy-measured and subjectively reported sleep duration (intraclass correlation coefficient = 0.72). 3 Polysomnography and ABPM were performed only at a single time point, which hindered a better understanding of the association between changes in sleep duration, sleep architecture, and BP.…”
Section: Figuresupporting
confidence: 61%
“…However, it has been found that children of this age are able to report quite well, at least on their food habits (42,43) . There is also a previous study showing that slightly older children are able to report their sleep duration (44) . Furthermore, the same questions on health behaviour have also been used in the HBSC study of 11-15-year-olds (29) .…”
Section: Discussionmentioning
confidence: 82%
“…Research views diary assessments as the "gold standard" for assessing sleep patterns (Knab & Engel-Sittenfeld, 1983;Wolfson et al, 2003). Recent studies have provided support for the reliability and validity of child completed daily sleep logs when compared to physiological measures, such as actigraphy (Gaina, Sekine, Chen, Hamanishi, & Kagamimori, 2004;Sadeh, Raviv, & Gruber, 2000).…”
Section: Sleepmentioning
confidence: 99%